Addressing special educational needs and disability in the curriculum. English - Hurst, Tim (London : Routledge, 2018)
"This book provides practical strategies and resources that have been proven effective in teaching English to pupils of all abilities, making English accessible, challenging and exciting. The author outlines important key principles that should underpin teaching and learning so that all pupils, including those with special educational needs, can enjoy the subject and make outstanding progress.The ideas and guidance draw on a wealth of experience, providing classroom activities and free online resources, which can be combined with different teaching approaches. A range of appendices provides teachers with real-life case studies and examples and templates for supporting pupils with SEND. Offering strategies that are specific to the context of English teaching, this book will enable teachers and their teaching assistants to:develop pupils' understanding by engaging multi-sensory approaches; ensure all pupils are able to participate fully in lessons and achieve success;design and use individual plans for pupils with SEND; assess and adapt content and resources when differentiating materials for pupils with a wide range of learning needs;use formative assessments to measure learning and inform planning.An invaluable tool for whole-school continuing professional development, this fully revised text will be essential for teachers and their teaching assistants seeking guidance specific to teaching English to all pupils, regardless of their individual needs. This book will also be of interest to SENDCOs, learning support units and senior management teams as well as to teacher-training professionals."--Provided by publisher.
chapter Introduction -- chapter 1 Meeting special educational needs: your responsibility -- chapter 2 The inclusive English classroom -- chapter 3 Accessing the examination curriculum -- chapter 4 Using ICT to support learners -- chapter 5 Monitoring and assessment -- chapter 6 Managing support.
"A David Fulton Book"--Cover.
Keywords: English -- Study and teaching; Children with disabilities -- Education; Special education